Predation Efficiency of Insect Predators in Suppressing Red Mite, Tetranychus bioculatus Attacking Marigold - Taleb, MA; Sardar, MA (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Experiments were conducted to find out the efficiency of predators, Stethorus punctillum and Micraspis discolor in searching (behaviour), handling (time) and predating (efficiency) red mite, Tetranychus bioculatus (Wood-Mason) attacking marigold plants. Predators grub and adults spent their time through walking, running and flying for searching prey. The walking was common in both the stages and it was more common in S. punctillum than M. discolor. The grub and adult of S. punctillum were more active than that of M. discolor for searching prey. The handling times were measured by adding time required for recognition, capture and consumption of the prey. The predators recognized prey in 2.2-3.0 minutes after release. The capture and consumption time differed significantly. The study showed significantly different preying activity of predators on egg, larva, nymph and adult of red mite. The predating efficiency of S. punctillum and M. discolor was significantly higher when feeding on eggs and was ranged from 35.4 to 48.4 eggs per day than that of larva, nymph and adult of the mite. The rate of consumption of red mite by S. punctillum and M. discolor increased with increasing density of mite up to 30 mites and was correlated with its population density. Key words: Searching behaviour, handling time, predation efficiency, Stethorus punctillum, Micraspis discolor, red mite, marigold. DOI = 10.3329/jard.v5i1.1465 J Agric Rural Dev 5(1&2), 98-104, June 2007